NON-FORMAL EDUCATION IN KOYSHA - Haileselassie, woldegerima (The Ethiopian Journal of Education, 2025)
Taking Koysha as its subject of study, this article attempts to investigate the status of basic literacy and skill-training in the region. Degree of participation and attendance, reasons for attending and problems encountered were examined to assess the status. Concerning skill-tr.atning, types of training given by the CSTCs in the light of established objectives, impact of training offered and attitude of people towards such training were assessed A descriptive survey method was used to collect data. Despite successive attempts made to tackle illiteracy in the past, the results suggest that the impact is still very low. The analysis reveals that satisfactory results were not achieved mainly due to the ad-hoc approach of the programme and lack of commitment of those involyed To ensure future success, the article proposes. a strategic approach toward integration of the formal and the non-formal educational sectors so that literacy programmes and skill-training could have proper direction and appropriate organisation. To effect this, schools should serve as mission centres, and traditional institutions and pertinent local government organisations should be actively involved.